Post Covid-19 Pandemic Economic Growth With Human Capital As A Long Term Drive - Lambok DR Tampubolon (Universitas Udayana, 2024)
The latest direction in development economics research both at home and abroad is starting to reduce the use of convoluted analytical models. Using too many variables but with unclear causality will actually complicate the analysis and produce results that are not necessarily good and correct. There are quite a lot of scientific work findings that use dozens of variables, with statistically significant results, but if you examine the relationship many questions arise such as